THE ESTABLISHMENT PROCESS OF ISLAMIC THEOLOGY IN GERMAN UNIVERSITIES - Ibrahim Kocyigit , (Journal of Islamic, Social, Economics and Development, 2019)
After the recommendations on the Advancement of Theologies and Sciences concerned with Religions at German universities in 2010 the new subject, â€žIslamic Theologyâ€ is faced with different expectations by various interest groups from the very start. For politicians and media the mission of â€žIslamic Theologyâ€ is to train religious scholars, Imams, religious teachers and social workers. Together with this challenge, the new subject should give answers to questions relating to integration: Moreover, â€žIslamic Studiesâ€, a subject with a longer tradition feels itself in competition with â€žIslamic Theologyâ€œ. The Islamic organizations try to be a part of the decision making process. The expert representatives of the subject try to meet the different and sometimes even opposed expectations.